Student retention and dropout in Higher Education in Latin America and the Caribbean: A systematic review - Felipe René Munizaga Mellado; María Beatriz Cifuentes Orellana; Andrés Jacob Beltrán Gabrie (Arizona State University, 2018)
The phenomenon of student retention and dropout in the Latin American and Caribbean region entails significant social and economic repercussions, both for students and for society as a whole. Despite the importance it has acquired over the last few years, there is still no bibliographical review of a systematic and replicable methodology that allows us to understand the main results and conclusions of the various investigations within the region. For this reason, the present study aimed to describe variables and factors that have been associated with student retention and dropout in Higher Education in Latin America and the Caribbean. We found and analyzed 81 articles in Spanish and Portuguese published between 1990 and 2016, distributed in 10 countries and indexed in seven databases. A protocol applied by two independent researchers was used to organize the information. A total of 111 different variables associated with the phenomenon were found. These were grouped into the five factors proposed by the ALFA-GUIA Project: "Individual", "Academic", "Economic", "Institutional" and "Cultural". Among the factors, the one that predominates is the "Individual", which makes it necessary to improve the measurement of latent variables and the adaptation of instruments. The presence of the factors "Academic" and "Institutional" demand changes at the level of Higher Education Institutions attending the new students who enter. Finally, the "Economic" factor demands to ensure the financing of the studies. Along with the above, much of the research focuses on the characterization of students and very few analyze the result of interventions to reduce dropout. There is also an important discordance when defining and measuring this phenomenon. That is why it is necessary to establish common parameters for the central concept and its measurement, in addition to redefining ALFA-GUIA factors specifically the "Individual", "Academic" and "Cultural".